Biventricular Pulsus Alternans - Param Vidwan; George A. Stouffer (Cardiology Research and Practice)
Pulsus alternans is a rare hemodynamic condition characterized by beat-to-beat variability in systolic pressure. It is attributed to variations in stroke volume with alternate cardiac cycles and is typically seen in patients with advanced myopathic conditions. Left ventricular pulsus alternans is rare, and right ventricular pulsus alternans is even less common. There are only a few reports of biventricular pulsus alternans. We report the case of a 62-year-old female with a recent anterior wall myocardial infarction who had biventricular pulsus alternans at the time of cardiac catheterization.